2021
DOI: 10.26434/chemrxiv-2021-2lg87
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxygen Stable Electrochemical CO2 Capture and Concentration through Alcohol Additives

Abstract: Current methods for CO2 capture and concentration (CCC) are energy intensive due to their reliance on thermal cycles, which are intrinsically Carnot limited in efficiency. In contrast, electrochemically driven CCC (eCCC) can operate at much higher theoretical efficiencies. However, most reported systems are sensitive to O2, precluding their practical use. In order to achieve O2 stable eCCC, we pursued the development of molecular redox carriers with reduction potentials positive of the O2/O2- redox couple. Pri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Combining these CV analyses with the approach we employ using DFT, one can investigate the thermodynamics of different potential capture mechanisms and see if such a trade-off still persists. We also note that very recent work has shown that electrolyte additives such as alcohols offer another interesting means to tune electrochemical CO 2 capture thermodynamics, 39 and it will be interesting to explore the trade-off between redox potential and capture strength with that approach. Overall, our work reveals the trade-off between redox potential and the strength of electrochemical CO 2 capture, and provides a foundation for the design of improved molecules and materials that can mitigate greenhouse gas emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Combining these CV analyses with the approach we employ using DFT, one can investigate the thermodynamics of different potential capture mechanisms and see if such a trade-off still persists. We also note that very recent work has shown that electrolyte additives such as alcohols offer another interesting means to tune electrochemical CO 2 capture thermodynamics, 39 and it will be interesting to explore the trade-off between redox potential and capture strength with that approach. Overall, our work reveals the trade-off between redox potential and the strength of electrochemical CO 2 capture, and provides a foundation for the design of improved molecules and materials that can mitigate greenhouse gas emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in the context of electrochemical CO 2 capture, the chemical steps are less thermodynamically favourable as more EWGs are added, supporting a trade-off between redox potential and CO 2 affinity, as suggested by previous experimental work on functionalised benzoquinones. 11,19 To explore this result experimentally, we measured the CVs of unsubstituted AQ, 1,4-F-AQ and AQ-F 8 under N 2 and under CO 2 (Figure 3(c)). For all cases, the re-duction wave positions of the first electron transfer (6) remain unchanged in the presence and absence of CO 2 .…”
Section: Effect Of Tuning Quinone Electron Density On Electrochemical...mentioning
confidence: 99%
“…In these mechanisms, two electron transfer (E) steps occur before any chemical (C) CO 2 capturing step, which has been supported in previous CV analysis of EWG-substituted quinones at low CO 2 concentration. 17,[19][20][21]37 Since our goal is to mitigate side-reactions of reduced quinones with O 2 , our main interest is to add EWGs to stabilise the reduced quinones, increasing the likelihood of both electrochemical reduction steps being required prior to any CO 2 capture. The electrochemical reduction occurs as:…”
Section: A Reaction Scheme and The Oxyanion Nucleophilicitymentioning
confidence: 99%
See 2 more Smart Citations